Do green human resource management and self-efficacy facilitate green creativity? A study of luxury hotels and resorts. Issue 4 (3rd April 2022) - Farooq, Ramsha; Zhang, Zhe; Talwar, Shalini; Dhir, Amandeep
Abstract: Employees' green-oriented behavior can produce positive outcomes for sustainability in all sectors. However, the granularity of how such behaviors can be promoted is limited in the literature. Therefore, research explaining the effect of policies pursued by organizations and the effect of leadership on employee green-oriented behavior can be useful. This study addresses this need by drawing upon Social Cognitive Theory to examine the association of green human resource management (GHRM) with green creativity (GC). In addition, we examine the mediation effect of green self-efficacy (GSE) and the moderation effect of green transformational leadership (GTL) to provide robust insights into how organizations can motivate employees to generate innovative solutions to environmental challenges. The model is tested by analyzing multi-wave and multi-source data collected from luxury resorts and hotels. The findings confirm a positive association of GHRM with GC as well as the mediation effect of GSE on the association of GHRM and GC. However, the moderated mediation influence of GTL on the indirect effect of GHRM on GC is not supported. Our findings can help tourism organizations boost employees' creativity, which, in turn, can support the use of green processes and help these organizations become better aligned with sustainable development goals.